A randomised comparison of three doses of sublingual misoprostol on postpartum myometrial contractility. (16th November 2010) - Elati, AA; Weeks, AD
Abstract : Objectives: To compare the postpartum uterine activity and side effects of various doses of sublingual misoprostol with intramuscular oxytocin. Methods: 35 women who did not require augmentation and who delivered vaginally were randomised to receive 200, 400 or 600 μg of sublingual misoprostol Postpartum haemorrhage prophylaxis. These were compared with 14 women given 10 IU of intramuscular oxytocin. Immediately after placental delivery, a Koala intrauterine pressure catheter was inserted transcervically into the uterine cavity and the uterine pressure measured for 120 min. Other outcomes included temperature and measured blood loss. Results: Women's age, parity, gestational age and baby birth weight were not significantly different in the four groups. There was no difference in uterine pressure between the three misoprostol doses. However, the uterine pressure was significantly lower than oxytocin with all three doses for the first 10 min (p<0.008) and significantly higher than oxytocin from 50 to 120 min (p<0.008). A dose-related rise in the body temperature and chills were observed in the misoprostol groups, with 8.3%, 8.3% and 45% of women experiencing a fever >39°C with the 200, 400 and 600 μg doses respectively. Conclusion: Intramuscular oxytocin has the highest immediate postpartum uterine activity. Lower doses of misoprostol may be as effective as high doses and the severity of side effects were dose related. Clinical outcomes with low dose misoprostol should be further explored.